1952
DOI: 10.1021/jo01139a010
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATIONS ON STEROIDS. XVIII. CHLORIDES AND CYCLIC SULFITES IN THE SERIES OF 3β, 5, 19-TRIHYDROXYETIOCHOLANIC ACID. A CASE OF ASYMMETRIC SULFUR*1

Abstract: With the aim of preparing steroids of the 19-hydroxypregnane series, 3p ,5,19trihydroxyetiocholanic acid (I) (1) and some of its esters were subjected to various chemical reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The mixture was treated as described earlier to give the solid residue. 1 13 C NMR (75 MHz, CDCl 3 ) δ 28.3 (broad peak), 38. 9, 60.8, 102.0;IR (KBr) 1309, 1275, 1234, 1137, 828 cm −1 ; MS (FAB) m/z 311 (MH + ).…”
Section: Mol Equivmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixture was treated as described earlier to give the solid residue. 1 13 C NMR (75 MHz, CDCl 3 ) δ 28.3 (broad peak), 38. 9, 60.8, 102.0;IR (KBr) 1309, 1275, 1234, 1137, 828 cm −1 ; MS (FAB) m/z 311 (MH + ).…”
Section: Mol Equivmentioning
confidence: 99%
“…It was demonstrated in 1952 that sulfur in sulfites can be a stereogenic center because of its stabletetrahedral geometry [1]. Since then, many cyclic and acyclic sulfites with a stereogenic center have been prepared because of interest in their structures and applications to organic synthesis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of sulfur as a synthetic stereogenic center is due to its stable tetrahedral geometry. This was first clearly demonstrated in 1952 when the separation of steroidal epimeric sulfites was reported …”
Section: Introductionmentioning
confidence: 99%
“…More recent reports have demonstrated the importance of the differential reactivity of epimeric cyclic sulfites in organometallic additions, oxidations, and reactions with enzymes …”
Section: Introductionmentioning
confidence: 99%
“…and Ehrenstein(141) obtained chiral sulfites for the first time. They found that a mixture of the cyclic diastereomeric sulfites 95, separated by chromatography, is obtained on treatment of 34-5,19-trihydroxyetiocholanate 96 with thionyl chloride in the pyridine.…”
mentioning
confidence: 99%